Delay analysis in construction contracts - Keane, P. J.; Caletka, A. F. (Wiley Blackwell, United Kingdom, 2015)
This book is a practical guide to the process of delay analysis and includes an in-depth review of the primary methods of delay analysis, together with the assumptions that underlie the precise calculations required in any quantitative delay analysis.
Introduction -- Construction programmes --Identification of construction delays -- Analysis of construction delays -- Delay analysis techniques -- Problematic issues -- Effective presentation of delay analysis
Includes index.
Keywords: CONSTRUCTION INDUSTRY -- PLANNING; CONSTRUCTION CONTRACTS; PRODUCTION SCHEDULLING